OPTIMIZATION MANAGEMENT OF FORMAT OF MOTOR TRANSPORTATION SERVICE OF POPULATION IN SEASONAL CONDITIONS OF RESORT TESTING - Kravchenko,; Gura, (Revista Inclusiones, 2019)
In this paper, a rational approach to optimizing the format of motor transport services for the population (MTSP) in seasonal conditions of resort agglomerations is proposed. Moreover, a criterion for determining the absolute integral effect of optimization of the MTSP format in resort agglomerations (RA) has been developed.